2012
DOI: 10.1530/rep-11-0225
|View full text |Cite
|
Sign up to set email alerts
|

K+ efflux through two-pore domain K+ channels is required for mouse embryonic development

Abstract: Numerous studies have suggested that K C channels regulate a wide range of physiological processes in mammalian cells. However, little is known about the specific function of K C channels in germ cells. In this study, mouse zygotes were cultured in a medium containing K C channel blockers to identify the functional role of K C channels in mouse embryonic development. Voltage-dependent K C channel blockers, such as tetraethylammonium and BaCl 2 , had no effect on embryonic development to the blastocyst stage, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…This finding is consistent with molecular expression of K2P channels in epithelia of taste buds [17], airways [18][19][20], gastrointestinal mucosa [21] and human nephron [22]. In relation to reproductive physiology, various K2P channels have been reported in sperm [23] and blastocysts [24] where culturing mouse zygotes in media supplemented with K2P blockers or using siRNA to knockdown KCNK expression significantly inhibited mouse blastocyst formation [24]. Virtually undetectable levels of TRAAK expression in the cell line mirror low expression in peripheral organs compared with the brain where TRA-AK is highly expressed [14,25].…”
Section: Discussionsupporting
confidence: 83%
“…This finding is consistent with molecular expression of K2P channels in epithelia of taste buds [17], airways [18][19][20], gastrointestinal mucosa [21] and human nephron [22]. In relation to reproductive physiology, various K2P channels have been reported in sperm [23] and blastocysts [24] where culturing mouse zygotes in media supplemented with K2P blockers or using siRNA to knockdown KCNK expression significantly inhibited mouse blastocyst formation [24]. Virtually undetectable levels of TRAAK expression in the cell line mirror low expression in peripheral organs compared with the brain where TRA-AK is highly expressed [14,25].…”
Section: Discussionsupporting
confidence: 83%
“…However, relatively little is known on the function of specific channels and pumps during embryogenesis. Studies in model systems, such as mouse, chicken and Xenopus , indicate dynamic expression of ion channels and pumps during embryogenesis 4 5 6 —whereas studies on natural populations facing variable ecological conditions are essentially missing.…”
mentioning
confidence: 99%
“…However, given that the sensor device mechanically stresses the cell, the signalling response is likely to be dominated by mechanically gated ion channels. There are very few investigations into the role of ion-channel activity in embryonic development but potassium channels are known to exist [18,19,20]. Our results indicated that signal responses from mechanically stressing cells directly correlate to the movement of ions, specifically K+ ions in this case.…”
Section: Proof Of Concept Resultsmentioning
confidence: 59%